Adsubjectification of Speaker in Construction of Statements with Meaning of Necessity in Discourse of Russian Orthodox Preaching - V. A. Burtsev (Научный диалог)
The article is devoted to the speaker’s adsubjectification in discourse, namely the mechanism of sentence contextualization, in which the meaning is obligatorily expressed, completely predetermined by the semantic context in the form of presuppositions that limit or exclude intentionality. The relevance of the study is due to the need to study non-intentional variants of grammatical content that contradict established ideas about the manifestations of subjectivity in language and speech. The novelty of the work lies in the establishment of non-intentional variants of the use of sentences with non-propositional meanings. The study was conducted on the material of the texts of the Russian Orthodox sermon. The use of two types of sentences with predicates of necessity is studied. An approach is used that takes into account the correlation between the semantic functions of predicatives and causators. Adsubjectivation as a predetermination of the causator by the semantic context was revealed for both varieties. It has been established that in statements with an explicit causator, the necessity of an action is always determined by situational presuppositions; in utterances with implicit causators — preparatory conditions for a speech act. At the same time, the impossibility of subjective motivation for the need for action in the discourse of preaching is noted, since this generates semantically unacceptable statements. It is shown that the mechanism of adsubjectification unambiguously determines the semantic limits of statements in a sermon, which is considered as evidence of the cognitive commonality of the implicit components of the content of statements plan and religious ideas.